The Economy of Flesh: A reading of Adam´ Smith´´´´´´ s Theory of Moral Sentiments - Pimentel Chacón, Jonathan (2019)
This article presents a reading of Adam Smith´s (1723-1790) Theory of Moral Sentiments that demonstrates its theological adscription. Focusing on how Smith represents the savage, the means by which he theorizes the question of incarnation and the ways he links economic theory and theological economics, I introduce an entire model for how to read Smith´s political thinking. Keywords: Adam Smith, Economic Theology, Theory of Moral Sentiments, Incarnation, Economic Theory.